Hydrogen bonding in Polymeric Materials - Kuo, Shiao-Wei (John Wiley and Sons, Inc. : Wiley-VCH, 2018)
Summarizing our current knowledge of the topic, this book describes the roles and effects of hydrogen bonding in polymer materials by reviewing the latest developments over recent years. To this end, it discusses all relevant aspects from the fundamentals, via characterization, to properties and applications in various polymeric materials, including polymer blends, block copolymers, mesoporous materials, biomacromolecules and nanocomposites. Invaluable reading for scientists in polymers and materials as well as those working in macromolecular chemistry.- Resumé
Keywords: vodíková vazba; polymery; hydrogen bond; polymers; elektronické knihy; monografie; electronic books; monographs